(untitled) (Linguostylistic Studies, 2014)
The article presents the dictionary «Eternal words Ukrainian culture», particularly poetic texts Lesya Ukrayinka. The dictionary is dedicated lexicographical processing of basic cultural concepts, eternal words in the historical and semantic stylistic aspects. This combination and cross three planes: stylistic (texts of different genre and stylistic nature), semantic (study of mechanisms of semantic transformation of lexical items, learning semantic nuances of words in different contexts) and historical (texts of different time slices). In stattы given fragment of the first chapter dictionary - Section «Lohosvit» which contains information about concepts related to the spiritual sphere, with faith and morality of man. Named Transverse section dictionary covers the concept of a religious worldview, abstract concepts, operating in contexts Lesya Ukrayinka poetry. The semantics of the eternal words contained in the second chapter «microcosm» associated with a person of family ties (grandmother, grandfather, father, mother, daughter, son), activity (teacher, sower, chumak), and so on. The article contains a fragment of the third chapter of «Macrocosm», which recorded contexts poet associated with nature (water, fire, field, sun, desert, path, etc.) And society (science, education, music). Кey words: eternal words, concepts, poetic lyrics, idiohrafichnyy vocabulary, literary language, the history of Ukrainian language. References